Redistribution and human capital: The impact on long-run growth - Martins, António (2016)
Given the controversy around the effect of income inequality on economic growth, we analyze if government intervention towards its reduction is desirable. Moreover, we test if human capital is a major vehicle through which redistribution operates. Using data on 174 countries, from 1960 to 2008, we verify that those who redistribute more present higher levels of 10-year growth more frequently. We also find that redistribution has a statistically significant positive effect on growth, and this impact is higher in developing economies. We did not find evidence that human capital captures this positive impact, which supports that other vehicles are responsible for this effect.